The prevalence of KRAS and BRAF mutation in colorectal cancer patients in Bali - Ayu Dewi Ni Nyoman; Ni Made Pramita Widya Suksmarini; Anak Agung Ngurah Satya Pranata; Andreliano Yosua Rompis; I Wayan Juli Sumadi (Universitas Gadjah Mada, 2022)
Mutations in the KRAS (Kirsten rat sarcoma viral oncogene homolog gene) and BRAF (v‐Raf murine sarcoma viral oncogene homolog B1) gene play a significant role in primary resistance to colorectal cancer therapy. Around 85‐90% of KRAS mutations in colorectal cancer occur in exon 2 (codon 12 and 13), whereas approximately 96% of BRAF mutations occur in exon 15 codon 600 (V600E). This study aimed to determine the prevalence and mutation characteristics of the KRAS and BRAF genes in colorectal cancer patients in Bali. The DNA was isolated from 44 formalin‐fixed paraffin‐embedded colorectal cancer samples which were stored in the Department of Pathology, Sanglah General Hospital in 2017. Detection of mutation was carried out by polymerase chain reaction (PCR) and direct sequencing. Out of 44 samples, only 27 were successfully amplified and sequenced. Our findings showed six samples (22.2%) with mutated KRAS at codons 12 and 13 (including two samples with G12D, one sample with G12V, and three samples with G13D). Interestingly, we found three samples (11.1%) of BRAF mutation, including two samples with V600E mutation and one with V600L mutation. Taken together, our results showed that KRAS and BRAF mutations were identified and occurred exclusively. Further studies are essential to identify the correlation of these mutations with colorectal cancer prognosis and response to chemotherapy